Designing a Web-Based Information System for Umrah and Hajj Travel Agencies - Zuli Anugra, Denish; Marleen, Onny (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study focuses on the design and implementation of a web-based information system for the Sanematour Jakarta Umrah and Hajj Travel Agency. The system aims to improve the efficiency of administrative tasks such as pilgrim registration, travel package management, payment validation, and reporting. By utilizing the Waterfall model in system development, the study outlines the phases of planning, requirements analysis, design, implementation, testing, and maintenance. The system’s effectiveness was tested through Black Box Testing, which confirmed that the core features, including login modules, registration forms, payment verification, and report generation, functioned correctly with both valid and invalid inputs. The testing results demonstrated that the system was free of critical errors and met the expected operational requirements. The successful implementation of the system allows for more efficient management of data, better accessibility for pilgrims, and faster report generation, thereby enhancing overall service quality. It is concluded that the system contributes to the digital transformation of the travel agency, improving operational efficiency and customer satisfaction. The research also recommends further improvements such as automatic notification features and enhanced data security protocols for continuous system optimization.